Research on the high-quality development of Beijing-Tianjin-Hebei region based on SD model under the constraint of “dual carbon” target - Yang, Weiwei; Hei, Yingying (Frontiers in Environmental Science, 2024)
Low-carbon economy is the inevitable path for the development of Beijing-Tianjin-Hebei. The SD model of High-quality development in the Beijing-Tianjin-Hebei region was constructed based on the “dual carbon” goal, including capital input and environmental pollution index as influencing factors. Through simulation and prediction, the following results are obtained: (1) Through the production function of Cobb Douglas, Beijing-Tianjin-Hebei region is still in the stage of highly concentrated capital to promote economic development. (2) It is proved that under the baseline scenario, the overall carbon neutrality and carbon peaking targets of Beijing-Tianjin-Hebei are difficult to achieve. However, in the context of high-quality development, the Beijing-Tianjin-Hebei region can successfully achieve the target of carbon peak by 2035. (3) Under the high-quality development scenario, the carbon emissions will decrease after the carbon peak, and the growth of economic aggregate and the development of total carbon emissions will be decoupled. Through the carbon emission simulation of the Beijing-Tianjin-Hebei region, it can be found that high-quality development is the only way for the future coordinated development of the Beijing-Tianjin-Hebei region, which can provide certain enlightenment for the development direction of the Beijing-Tianjin-Hebei region.